The Hegemony of Western Pop Music in Indonesia 2010-2020 Period - Andre Ikhsano; Jeremy Asido Sianipar (Ikatan Sarjana Komunikasi Indonesia, 2021)
One of the strong and real cultural dominations in Indonesia is the dominance of Western pop music. In this case, there is a voluntary acceptance by the Indonesian people of Western pop music which leads to the concept of Gramsci's hegemony. The continuity of the hegemony of western pop music in the country has been going on for a very long time, for that of course there is a need for deeper advocacy of the hegemony of western pop music so that the Indonesian people are aware of the ‘colonialism’ of western pop music in the country. This critical paradigm research is supported by a qualitative approach based on the theory of hegemony and supported by the concept of cultural imperialism. The findings of this study are the hegemony of western pop music that is widespread and civil society, namely, the Indonesian people tend to accept it with joy so that it seems that it even perpetuates the hegemony itself. Meanwhile, in the aspect of political society (government), various efforts have been made in advancing the national music industry; but are still considered less than optimal.